Supply and demand for cereals in Pakistan 2010-2030 - Nazli, Hina; Haider, Syed Hamza; Sheik, Asjad Tariq (International Food Policy Research Institute, 2012)
Since the year 2000, Pakistan’s population has been growing at a rate that is higher than domestic food grain production. In view of the importance of wheat and rice in the human diet in Pakistan, it is extremely important to estimate the future demand and supply of both cereals. This paper presents the projections of future demand and supply for these two main cereals for 2010, 2015, 2020, 2025, and 2030.